2013
DOI: 10.1128/jb.00691-13
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline-Related Transcriptional Regulation of the CTnDOT Mobilization Region

Abstract: CTnDOT is a 65-kb conjugative transposon (CTn) in Bacteroides spp. that confers resistance to the antibiotics erythromycin and tetracycline (Tc). Conjugative transfer of CTnDOT is regulated upon exposure of cells to Tc. In the absence of Tc, no transfer is detectable; however, a cascade of regulatory events results in the conjugative transfer of CTnDOT upon Tc induction. Previous studies addressing regulation of CTnDOT conjugative transfer focused primarily on the 13-kb transfer (tra) operon, which encodes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…This is due largely to a repressor of conjugative transfer, the small RNA RteR. In addition, we recently showed that the CTnDOT-encoded integrase, IntDOT, may also inhibit conjugative transfer (42, 43). An overview of the CTnDOT transcriptional cascade is shown in Fig.…”
Section: Ctndot Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due largely to a repressor of conjugative transfer, the small RNA RteR. In addition, we recently showed that the CTnDOT-encoded integrase, IntDOT, may also inhibit conjugative transfer (42, 43). An overview of the CTnDOT transcriptional cascade is shown in Fig.…”
Section: Ctndot Overviewmentioning
confidence: 99%
“…Sequential deletion analysis of the excision operon demonstrates that an in-frame deletion of either xis2d or exc is sufficient to diminish mob transcription to the constitutive levels, while a deletion of either xis2c or orf3 has no effect (43). While both the mob operon and tra operon share a requirement for xis2d to enhance transcription, they differ in that the mob operon also requires exc , and the tra operon requires xis2c in addition to xis2d (Fig.…”
Section: Ctndot Overviewmentioning
confidence: 99%
“…However, Xis2c and Xis 2d have also been identified as positive regulators of the tra genes that encode proteins involved in conjugation (6). In addition, Xis2d and Exc also appear to stimulate expression of the mob operon that encodes the relaxase and coupling proteins required for mobilization (7). CTnDOT also encodes two antibiotic resistance genes, tetQ and ermF (8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of either orf3 or exc had no effect on the transcriptional regulation of the tra genes (16). Recent studies showed that Xis2d and Exc are responsible for positively regulating the transcription of the mob operon (18). The mob operon consists of three genes ( mobA - mobB - mobC ) that encode proteins in the relaxosome complex, which is responsible for transferring the CTnDOT DNA to the mating apparatus (18, 19).…”
Section: 1 Introductionmentioning
confidence: 99%
“…Recent studies showed that Xis2d and Exc are responsible for positively regulating the transcription of the mob operon (18). The mob operon consists of three genes ( mobA - mobB - mobC ) that encode proteins in the relaxosome complex, which is responsible for transferring the CTnDOT DNA to the mating apparatus (18, 19). Deletions of either xis2c or orf3 have no effect on the transcriptional regulation of the mob genes (18).…”
Section: 1 Introductionmentioning
confidence: 99%